Towards the Dispersion Characteristics of Tapered Core Dielectric Optical Fibers - Lim, M. H.; Yeow, S. C.; Choudhury, P. K.; Kumar, D. (2006)
Using Maxwell's field equations, an analytical investigation is presented of the modal characteristics for a step-index plastic clad tapered optical fiber operating in the infrared region of the electromagnetic spectrum. Following rigorous analytical approach, dispersion relations are developed, and a study is presented of the fiber characteristics for different lower order modes. The cutoff situation is also discussed. Attention is also paid to the characteristics of dispersion curves for the tapered fiber under consideration by taking into account the different possible modes. Results are compared with conventional optical fibers in terms of dispersion characteristics.